A Neutrophil Extracellular Traps Signature Predicts the Clinical Outcomes and Immunotherapy Response in Head and Neck Squamous Cell Carcinoma - Chen, Naifei; He, Dongsheng; Cui, Jiuwei (Frontiers in Molecular Biosciences, 2022)
Background: Neutrophil extracellular traps (NETs) play an important role in the occurrence, metastasis and immune escape of cancers. This study aimed to investigate NET-related genes, their clinical prognostic value and their correlation with immunotherapy and anticancer drugs in patients with head and neck squamous cell carcinoma (HNSCC). Methods: Differentially expressed NET-related genes in HNSCC were identified based on multiple public databases. To improve the clinical practicability and avoid overfitting, univariable, least absolute shrinkage and selection operator (LASSO) and multivariable Cox algorithms were used to construct a prognostic risk model. A nomogram was further used to explore the clinical value of the model. Internal and external validation were conducted to test the model. Furthermore, the immune microenvironment, immunophenoscore (IPS) and sensitivity to anticancer drugs in HNSCC patients with different prognostic risks were explored. Results: Six NET-related genes were screened to construct the risk model. In the training cohort, Kaplan–Meier (K-M) analysis showed that the overall survival (OS) of low-risk HNSCC patients was significantly better than that of high-risk HNSCC patients (P<0.001). The nomogram also showed a promising prognostic value with a better C-index (0.726 vs. 0.640) and area under the curve (AUC) (0.743 vs. 0.706 at 3 years, 0.743 vs. 0.645 at 5 years) than those in previous studies. Calibration plots and decision curve analysis (DCA) also showed the satisfactory predictive capacity of the nomogram. Internal and external validation further strengthened the credibility of the clinical prognostic model. The level of tumor mutational burden (TMB) in the high-risk group was significantly higher than that in the low-risk group (P=0.017), and the TMB was positively correlated with the risk score (R=0.11; P=0.019). Moreover, the difference in immune infiltration was significant in HNSCC patients with different risks (P<0.05). Furthermore, the IPS analysis indicated that anti-PD-1 (P<0.001), anti-CTLA4 (P<0.001) or combining immunotherapies (P<0.001) were more beneficial for low-risk HNSCC patients. The response to anticancer drugs was also closely correlated with the expression of NET-related genes (P<0.001). Conclusion: This study identified a novel prognostic model that might be beneficial to develop personalized treatment for HNSCC patients.